Lessons learned from the successful countries and distinguished authors by reviewing 2007-2016 journal publications on mobile technology-supported collaborative learning. (2018) - Fu, Qing-Ke
In this study, a review of mobile collaborative learning was conducted to identify the main contributing countries and authors of this field by analysing journal papers published from 2007 to 2016. Based on the analysis results, the outstanding countries and authors are presented; more important, the key factor of successfully promoting mobile learning studies and applications in a country was investigated. The findings and suggestions of this study could provide a good reference for policy makers and administrators who intend to implement successful mobile learning research and practice in their countries.